A decision making model for assesing the influence of steaming speed on the revenue performance of tanker on time charter/ Rudiah Md Hanafiah - Md Hanafiah, Rudiah (Institute of Graduate Studies, UiTM, 2017)
Transporting cargo by maritime transportation has been met with uncertain conditions that have influenced not only the movement volumes but also the expenditure cost and revenues. Therefore, speed reduction has been used as a strategy to solve this problem, particularly for the container and tanker sectors. Accordingly, studies related to speed reduction have increased rather vastly and have involved various pertinent aspects, such as the economic model and environmental impact. However, among these studies, none has looked into the benefits of speed reduction for small-sized vessel, particularly from time charter perspective and from the consideration of shorthaul trading routes. The current study addresses this issue through a number of real-test cases and the Malaysian petrochemical industry was chosen as the subject matter. The objectives of this study are to (1) identify the factors that affect the revenue performance of tanker on time charter, (2) analyse the impact of the contributing factors on the revenue performance of tanker on time charter, (3) evaluate the impact of implementing speed reduction on the revenue performance of tanker on time charter, and (4) develop a decision-making model that is most suitable for tanker on time charter.